A quality improvement initiative to increase pneumococcal vaccination coverage among children after kidney transplant. (22nd June 2016) - Malone, Kathryn; Clark, Stephanie; Palmer, Jo Ann; Lopez, Sonya; Pradhan, Madhura; Furth, Susan; Kim, Jason; Fisher, Brian; Laskin, Benjamin
Abstract: Pneumococcal vaccination rates among children receiving a kidney transplant remain suboptimal. Current practice guidelines in the United States recommend giving the PPSV23 after priming with the PCV13. We conducted a QI initiative to increase pneumococcal vaccine rates in our kidney transplant recipients by developing an age‐based vaccine algorithm, obtaining vaccine records, and generating reminders for patients and clinicians. A monthly report from the EHR tracked outcomes. The process metric was missed vaccine opportunities, and the overall objective was to improve coverage with both the PCV13 and PPSV23. Over the first six months, we increased the percentage of visits where the vaccine was given from a baseline of 4% to 33%. However, by the end of the 12‐month period, the percentage of eligible visits where the vaccine was given decreased to 8.7%. Nevertheless, over the 12‐month observation period, we were able to increase the percentage of transplant patients receiving the PCV13 and PPSV23 from 6% to 52%. Utilizing an age‐based algorithm and the electronic medical record, vaccine champions can track both missed visit opportunities and the number of vaccinated patients to improve pneumococcal immunization coverage for these high‐risk patients.